(untitled) (Theatrum historiae, 2015)
The study deals with the phenomenon of brigandage and robbery in Hungarian-Polish border area in the 15th century. The royal town of Bardejov and its activities directed against brigands and criminal groups operating in the mentioned space are in the focus of interest. On the basis of source analysis, the author pursues ethnic and social affiliation of members of the brigand troops. She also points out the nobility involvement in the development of brigandage in the aforesaid period. The particular examples of the activities of brigand groups related to Bardejov are put into the context of so far published findings about the medieval history of the town.